ON SUPER (3n+5,2)- EDGE ANTIMAGIC TOTAL LABELING AND IT’S APPLICATION TO CONSTRUCT HILL CHIPER ALGORITHM - Prihandini, Rafiantika Megahnia; Adawiyah, Robiatul (PATTIMURA UNIVERSITY, 2023)
Graph labeling can be implemented in solving problems for various fields of life. One of the application of graph labelling is in security system. Information security is needed to reduce risk, data manipulation, and unauthorized destruction or destruction of information. Cryptographic algorithms that can be used to build security systems, one of the cryptographic algorithms is Hill Cipher. Hill chipper is a cryptographic algorithm that uses a matrix as a key to perform encryption, decryption, and modulo arithmetic. This study discusses the use of Super (3n+5,2)- edge antimagic total labeling to construct the Hill Chiper algorithm. The variation of the edge weight function and the corresponding edge label on the graph, will make the constructed lock more complicated to hack